2016
DOI: 10.1155/2016/5678193
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Expansion Measurements in Fresh and Saline Ice Using Fiber Optic Strain Gauges and Multipoint Temperature Sensors Based on Bragg Gratings

Abstract: This paper describes the use of Fiber Bragg Grating (FBG) sensors to investigate the thermomechanical properties of saline ice. FBG sensors allowed laboratory measurements of thermal expansion of ice samples with a range of different sizes and geometries. The high sampling frequency, accuracy, and resolution of the FBG sensors provide good quality data across a temperature range from 0 ∘ C to −20 ∘ C. Negative values of the effective coefficient of thermal expansion were observed in ice samples with salinities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Negative thermal expansion of saline ice with salinities of 6 and 9.4 ppt was reproduced in laboratory experiments when the ice temperature was higher than −5°C [ 13 , 20 ]. The values of ECTE were found to be about −10 −4 K −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative thermal expansion of saline ice with salinities of 6 and 9.4 ppt was reproduced in laboratory experiments when the ice temperature was higher than −5°C [ 13 , 20 ]. The values of ECTE were found to be about −10 −4 K −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Upward migration of the brine through the ice was caused by water overpressure in the tank when growing ice was frozen to the tank walls. Artificial pumping of the water pressure below the ice caused visible migration of brine through the ice and the increase of its surface temperature by 0.7°C [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…FBG temperature strings with 12 distributed thermistors distributed inside a metal tube and an FBG strain sensors were used in the tests (Advanced Optics Solutions GmbH, Dresden, Germany) [72]. Neighboring thermistors of FBG temperature strings are spaced 1 cm apart.…”
Section: Fiber Bragg Grating Sensorsmentioning
confidence: 99%
“…However, it can be influenced by many factors, such as the spectral line width, the disturbance of the laser array, and the dispersion characteristics of the grating [9][10][11][12]. As the powers of the laser array are increased, the grating thermal deformation, which induces degeneration of the combined beam quality, becomes more significant [13][14][15]. Zhou et al reported the modulation of combined beam characteristics by volume Bragg gratings with thermal deformation.…”
Section: Introductionmentioning
confidence: 99%